Considerable use of computers and the Internet in managing public relations activities The Ministries of Justice and the Interior are examples - الخاقاني حسن عبد الهادي (ALBAHITH ALALAMI, 2015)
She noted most of the results of research conducted on the use of computers and the Internet in the areas of administrative, economic, agricultural and educational to a significant improvement in learning outcomes of these groups in the development of mechanisms of action, has increased rates of computer use and applications in various spheres of life at very fast pace so that the computer and the Internet is a vital part of any activity, whether administrative or research or the media, hence it can be said that the use of computers and the Internet in the management of public relations activities in any organization can accelerate the pace of echo positive goals and purposes of public relations, this study comes to looking at usage levels studied computer and the Internet at management public relations activities in government institutions through the study of sections of public relations in the ministries of justice and interior model, also shed light on the role that can be played by use studied computer and the Internet in the development of management public relations activities in the institutions of the state, and the extent to which this use in the development of skills knowledge of its employees, and the attic lies the importance of this study is to contribute effectively in the development process and the development of management public relations activities in the press institutions represented by the ministries of Justice and Interior and what they offer insights and future prospects for the development of the administrative area and communication using technical means of a computer and the Internet in a measured way and resulting from this use of positive effects on workers in the departments of public relations is to develop their abilities and their cognitive skills more than one way traditional education, has used the study curriculum descriptive to describe the process of using computers and the Internet in public relations activities in the ministries mentioned above, using the research of application form questionnaire containing a series of questions regarding the use of computers and the Internet and how to use this, this study has reached to a number of results that enhance the deliberate and planned use of information and communication technology in the management of public relations activities.